"Most Americans like their privacy." Exploring privacy concerns through US guests' reviews. Issue 8 (26th July 2021) - D'Acunto, David; Volo, Serena; Filieri, Raffaele
Abstract : Purpose: This study aims to explore US hotel guests' privacy concerns with a twofold aim as follows: to investigate the privacy categories, themes and attributes most commonly discussed by guests in their reviews and to examine the influence of cultural proximity on privacy concerns. Design/methodology/approach: This study combined automated text analytics with content analysis. The database consisted of 68, 000 hotel reviews written by US guests lodged in different types of hotels in five European cities. Linguistic Inquiry Word Count, Leximancer and SPSS software were used for data analysis. Automated text analytics and a validated privacy dictionary were used to investigate the reviews by exploring the categories, themes and attributes of privacy concerns. Content analysis was used to analyze the narratives and select representative snippets. Findings: The findings revealed various categories, themes and concepts related to privacy concerns. The two most commonly discussed categories were privacy restriction and outcome state. The main themes discussed in association with privacy were "room, " "hotel, " "breakfast" and several concepts within each of these themes were identified. Furthermore, US guests showed the lowest levels of privacy concerns when staying at American hotel chains as opposed to non-American chains or independent hotels, highlighting the role of cultural proximity in privacy concerns. Practical implications: Hotel managers can benefit from the results by improving their understanding of hotel and service attributes mostly associated with privacy concerns. Specific suggestions are provided to hoteliers on how to increase guests' privacy and on how to manage issues related to cultural distance with guests. Originality/value: This study contributes to the hospitality literature by investigating a neglected issue: on-site hotel guests' privacy concerns. Using an unobtrusive method of data collection and text analytics, this study offers valuable insights into the categories of privacy, the most recurrent themes in hotel guests' reviews and the potential relationship between cultural proximity and privacy concerns.